Surgical Safety Toolkit based Quality Monitoring of Fistula Surgery in Bangladesh - Jahan, Israt; Huda, Sk Nazmul; Romanzi, Lauri (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To share our experience using a new tool to monitor quality in a surgical care delivery system and document fistula surgery-related mortality and morbidity. Methods: Surgeons, nurses and other clinical care providers were trained to use SST for every client they served at seven facilities. From April 2017 to June 2018, data were captured for 283 clients across these facilities. Anonymous SST data were centrally collected, entered in a spreadsheet and summarized. Results: Among 283 fistula patients, who had repair surgery, 27 morbidities were recorded and there was no mortality. 44% of morbidities were related to intra/post-operative hemorrhage requiring blood transfusion, 30% were repair wound breakdown. The SST documented that all women who had fistula surgery received counseling on follow-up care, the importance of abstinence during the recovery period and on family planning. Conclusions: The SST is derived from global standards for safe surgical care with a focus on fistula-specific metrics. This toolkit can be used for routine documentation of surgical care processes for fistula cases and be adapted for monitoring other types of surgical care. Keywords: fistula surgery, monitoring, surgical safety kit.